Preparation of Zeolite Type 13X from Locally Available Raw Materials - R.Ugal, Jalil .; Mustafa, Malik; A.Abdulhadi, Ali. (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The aim of this work was to prepare zeolite type 13X from locally available kaolin and to study the effects of using some binding materials through the process of agglomeration of this zeolite. This study was focused on using kaolin binder in different weight percents (10,15,25,35 and 45%).Physical and mechanical properties of the agglomerates such as porosity , apparent density , pore volume, crushing strength , loss on attrition , surface area and finally the adsorption capacity had been measured and evaluated .The preparation step was achieved by mixing the reactants consisting of metakaolin , source of silica as ( sodium trisilicate ) and sodium hydroxide . The conditions was temperature of 70° C and time of mixing as 8, 10,24,34,50,65,75 and 80 hours .The zeolite –binder was shaped in the form of cylindrical particles of 2.5 mm in diameter and 4-8 mm long using a suitable experimental technique . It was found that the suitable binder kaolin clay with 25% by weight. This gave the best properties as crushing strength, adsorption capacity and density compared with standard properties of zeolite 13X.